Prevalence of subchondral bone pathological changes in the distal metacarpi/metatarsi of racing Thoroughbred horses. Issue 10 (26th September 2017) - Bani Hassan, E; Mirams, M; Mackie, EJ; Whitton, RC
Abstract : Objectives: To investigate the prevalence of microscopic subchondral bone injury in the distal metacarpi/tarsi of Thoroughbred racehorses and associations with recent and cumulative training history. Methods: Metacarpi/metatarsi were obtained from postmortem examination of Thoroughbred racehorses. The severity of palmar/plantar osteochondral disease (POD) was graded in forelimbs from 38 horses and in hindlimbs from a separate cohort of 45 horses. Forelimb samples were embedded in methyl methacrylate and examined using backscattered scanning electron microscopy. Microfracture density in the condylar subchondral bone was determined. Horizontal subchondral bone fractures were identified in hindlimb samples using sections of demineralised tissue. Empty osteocyte lacunae were quantified in hindlimb samples using sections of demineralised tissue. Results: The prevalence of gross POD was 65.8% (95% confidence interval (CI) 48.7–80.4%) in the forelimb and 57.8% (95% CI 42.2–72.3%) in the hindlimb cohort of horses. Microfractures occurred in the forelimbs of 97.4% (95% CI 86.2–99.9%) of horses. Microfracture density in forelimbs increased with age (rs  = 0.50, P = 0.001), the number of race starts (rs   =  0.47, P = 0.003) and was greater in the medial condyles of horses in training than in those not in training (n = 21, median: 3.1/mm; range: 0.8–10.0 vs n = 17, 1.4/mm; 0–4.5, P = 0.008). Empty osteocyte lacunae were observed in the subchondral bone of hindlimbs in 97.7% (95% CI 88.0–99.9%) of 44 horses. Conclusions: Subchondral bone pathology occurs with a high prevalence in Thoroughbred racehorses presented for postmortem examination. The accumulation of subchondral bone damage with longer career duration is consistent with bone fatigue.